Level of self esteem among medical students in International Islamic University Malaysia (IIUM) and its association with religiosity - Amiruddin, Amirah; Mustapa, Nurul Fitri; Abdul Hadi, Azwanis; Zainal Abidin, Muhammad 'Adil (2020)
Self-esteem is an essential aspect of wellbeing1 particularly for medical students5 who are susceptible to mental disorders. In Islam, self-esteem is built with the combination of both revelation by Allah and human’s effort. 6 With the increasing study in terms of religiosity and self-esteem2,3,4, the role of religiosity as possible protective factor for Muslim medical students in their life, is a stepping stone towards becoming competent Muslim professionals.